How does internationalization begin? The role of age at entry and export experience in the early stages of the process - José C. Casillas; Francisco J. Acedo; M. Ángeles Rodríguez-Serrano (BRQ Business Research Quarterly, 2020)
This article deals with two important concepts in the prior literature on the internationalization process: age at entry and export experience. Against previous research, we analyze how both of them influence simultaneously international behavior in the early stages of the internationalization process as a trade-off. For that aim, we analyze the influence of both variables on international behavior in the early stages of the internationalization process, from a dynamic perspective, looking at initial export behavior and speed during this period. We analyze export development process of 106 Spanish small and medium-sized enterprises (SMEs), most of them international new ventures, in their first 8 years of export activity, combining the effect of age at entry and experiential learning during this period, finding that age at entry and export experience exert not only a direct effect but also a moderation influence on initial export development, observing a trade-off between such influence as experience grows.
Keywords: M16; 650; Age at entry; export behavior; International New Ventures; longitudinal research; learning